2007
DOI: 10.1186/1471-2350-8-55
|View full text |Cite
|
Sign up to set email alerts
|

PPARα L162V underlies variation in serum triglycerides and subcutaneous fat volume in young males

Abstract: Background: Of the five sub-phenotypes defining metabolic syndrome, all are known to have strong genetic components (typically 50-80% of population variation). Studies defining genetic predispositions have typically focused on older populations with metabolic syndrome and/or type 2 diabetes. We hypothesized that the study of younger populations would mitigate many confounding variables, and allow us to better define genetic predisposition loci for metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
5
28
2
Order By: Relevance
“…The PPARα V162V genotype was found to be absent in our study, consistent with our previous study 7 and previous studies among Caucasians 13 and African Americans, 14 while the V162 allele was found to be absent among African Senegalese. 15 Meanwhile, despite having similar demographics with Malaysia, Chan et al 16 reported lower MAFs for this SNP -.005/.004/.02 in Singaporean Malays/Chinese/Indians.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The PPARα V162V genotype was found to be absent in our study, consistent with our previous study 7 and previous studies among Caucasians 13 and African Americans, 14 while the V162 allele was found to be absent among African Senegalese. 15 Meanwhile, despite having similar demographics with Malaysia, Chan et al 16 reported lower MAFs for this SNP -.005/.004/.02 in Singaporean Malays/Chinese/Indians.…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, in Caucasian populations, MAF ranged from .06 to .08. 13,[18][19][20][21] In agreement with our current and previous findings, 7 PPARα L162V SNP was not associated with obesity in the Chinese Han, 17 Brazilians 22 and Caucasians. 4,[23][24][25] Furthermore, a study conducted by Robitaille et al 23 reported no association of this SNP with Met-S among Caucasian men, consistent with our current finding.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…More precisely, the variations in total cholesterol, (apo) A-I and cholesterol concentrations in small LDL particles between individuals could be explained by the PPAR ␣ L162V polymorphism [5] . Other studies have also suggested that the PPAR ␣ L162V polymorphism was associated with increases in lipid concentrations [6][7] . These data suggest that genetic variations of the gene encoding the PPAR ␣ may also modulate the CVD risk profile [8] .…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that this variability in the response to diet is partly attributable to genetic factors [3] . Possible genetic variants, which may impact on the lipid response to treatment, are, among others, polymorphisms in genes encoding apolipoprotein (apo) E [4] and peroxisome proliferator-activated receptor-␣ (PPAR ␣ ) [5][6][7] . Of particular interest to the current research is an earlier study, which reported that the plasma lipoprotein/lipid responsiveness to a modification in the ratio of polyunsaturated to saturated fatty acids (FA) was influenced by the PPAR ␣ gene [5] .…”
Section: Introductionmentioning
confidence: 99%